PROTEKSI MEMORI DAN CPU TERHADAP KESALAHAN PROGRAM PADA SISTEM OPERASI - Septilia Arfida (IIB Darmajaya, 2011)
Operating system has began to divides the system resources to many programs simultaneously to improve system performance. But when the system runs without resource sharing, an error in the program will only cause problems in the program. Along with development of the operating system, then the overall control system is given to the operating system. In general, the memory need to be protected for the operating system accesses protected from user programs and also to protect user programs with one another. The program – a program the user can access directly to the Central Processing Unit to execute intructions. When a program error appears, the operating system must abnormally terminate the program, provide appropriate error messages, and frees memory used by the program. Keywords: Memory Protection, Protection of Central Processing Unit, Operating System